Analysis of Differences Between CR, DER, NPM, TATO on the Financial Performance of Telecommunication Companies Listed on the IDX During Covid-19 - Juniarti, Septiani; Diporini, Vidya Ayu; Parmariza, Yenida Parmariza (Kirana Publisher (KNPub), 2024)
This research aims to analyze differences in CR, DER, NPM, TATO on the financial performance of telecommunications companies in Indonesia during Covid 19. The population used in the research is telecommunications sector companies listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling technique. The data collection method is using secondary data originating from financial reports that have been published by the company via the official website www.idx.co.id. This research proves that Covid-19 does not cause the financial performance of telecommunications companies listed on the Indonesia Stock Exchange (BEI) to increase or decrease significantly, whether seen from the Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM). ), Total Asset Turnover Ratio (TATO). However PT. Telekomunikasi Indonesia Tbk. is the best company since Covid-19 because of the number of people consuming internet packages at PT. Telecommunications continues to improve. This result can be seen from the Net Profit Margin (NPM) ratio, where the net profit of PT. Telekomunikasi Indonesia Tbk. continue to increase.